Inherent duality of vesiculation kinematics revealed through 4D imaging - Mathieu Colombier; Francisco Cáceres; Janine Birnbaum; Rebecca deGraffenried; Yan Lavallée; Jackie E. Kendrick; Bettina Scheu; Simon Thivet; Pedro Valdivia; Ruben M. Ruhekenya; Christian M. Schlepütz; Jonathan M. Castro; et al. (Journal of Volcanology and Geothermal Research, 2026)

The role of submarine volcanism in atmospheric chemistry - M. Colombier; M. Bonifacie; M. Brenna; A. Burke; C. Cimarelli; S.J. Cronin; P. Delmelle; D.B. Dingwell; K-U. Hess; M. Huebsch; T. Kula; F. Latu’ila; et al. (Earth and Planetary Science Letters, 2025)

Conduit processes in crystal-rich dacitic magma and implications for eruptive cycles at Guagua Pichincha volcano, Ecuador - M. Colombier; B. Bernard; H. Wright; J. L. Le Pennec; F. Cáceres; C. Cimarelli; M. J. Heap; P. Samaniego; J. Vasseur; D. B. Dingwell (Bulletin of Volcanology, 2022)
Stratovolcanoes are commonly characterised by cyclic eruptive activity marked by transitions between dome-forming, Vulcanian, Subplinian and Plinian eruptions. Guagua Pichincha volcano (Ecuador) has been a location of such cyclicity for the past ~ 2000 years, with Plinian eruptions in the first and tenth centuries AD (Anno Domini/after Christ), and CE (Common Era) 1660, which were separated by dome-forming to Subplinian eruptions, such as the recent 1999–2001 eruption. These cycles are therefore a prominent example of effusive-explosive transitions at varying timescales. Here, we investigate the reasons for such shifts in activity by focusing on degassing and outgassing processes within the conduit. We have coupled a petrophysical and textural analysis of dacites from the CE 1660 Plinian eruption and the 1999–2001 dome-forming/Vulcanian eruption, with different percolation models in order to better understand the role of degassing on eruptive style. We demonstrate that the transition from dome-forming to Plinian activity is correlated with differences in phenocryst content and consequently in bulk viscosity. A lower initial phenocryst content and viscosity is inferred for the Plinian case, which promotes faster ascent, closed-system degassing, fragmentation and explosive activity. In contrast, dome-forming phases are promoted by a higher magma viscosity due to higher phenocryst content, with slower ascent enhancing gas escape and microlite crystallization, decreasing explosivity and yielding effusive activity. Resumen Los estratovolcanes se caracterizan comúnmente por presentar actividad eruptiva cíclica, marcada por transiciones entre erupciones formadoras de domos y erupciones de tipo Vulcanianas, Subplinianas y Plinianas. El volcán Guagua Pichincha (Ecuador) ha dado lugar a tal ciclicidad durante los últimos ~ 2000 años, con erupciones Plinianas tanto en los siglos Primero y Décimo, como en el año 1660, las cuales estuvieron intercaladas por erupciones formadoras de domos y de tipo Subplinianas, tal como ocurrió durante la erupción reciente de 1999–2001. Estos ciclos son, por lo tanto, ejemplos destacados de transiciones eruptivas de tipo efusiva-explosiva a escalas de tiempo variadas. En este trabajo, investigamos las razones de tales cambios de actividad enfocándonos en procesos de exsolución y pérdida de gases del magma en el conducto (desgasificación en sistemas cerrado y abierto). Hemos acoplado análisis petrofísicos y texturales tanto de dacitas de la erupción Pliniana de 1660, como de la erupción formadora de domos/Vulcaniana de 1999–2001, junto con diferentes modelos de percolación, para así comprender mejor el rol de la exsolución de volátiles en el estilo eruptivo. Demostramos que la transición desde una actividad efusiva formadora de domos a una Pliniana está correlacionada con diferencias en el contenido de fenocristales y, subsecuentemente, con la viscosidad total del magma. Un contenido inicial menor de fenocristales y una menor viscosidad se infiere para el caso Pliniano, lo que promueve un ascenso más rápido, desgasificación en sistema cerrado, fragmentación y finalmente actividad explosiva. Por el contrario, las fases formadoras de domos son promovidas por una viscosidad mayor debido a un contenido mayor de fenocristales, con ascenso más lento promoviendo a su vez el escape de gases y la cristalización de microlitos, disminuyendo la explosividad y produciendo actividad efusiva.

In situ observation of the percolation threshold in multiphase magma analogues - M. Colombier; F. B. Wadsworth; B. Scheu; J. Vasseur; K. J. Dobson; F. Cáceres; A. Allabar; F. Marone; C. M. Schlepütz; D. B. Dingwell (Bulletin of Volcanology, 2020)
Magmas vesiculate during ascent, producing complex interconnected pore networks, which can act as outgassing pathways and then deflate or compact to volcanic plugs. Similarly, in-conduit fragmentation events during dome-forming eruptions create open systems transiently, before welding causes pore sealing. The percolation threshold is the first-order transition between closed- and open-system degassing dynamics. Here, we use time-resolved, synchrotron-source X-ray tomography to image synthetic magmas that go through cycles of opening and closing, to constrain the percolation threshold Φ C at a range of melt crystallinity, viscosity and overpressure pertinent to shallow magma ascent. During vesiculation, we observed different percolative regimes for the same initial bulk crystallinity depending on melt viscosity and gas overpressure. At high viscosity (> 10 6 Pa s) and high overpressure (~ 1–4 MPa), we found that a brittle-viscous regime dominates in which brittle rupture allows system-spanning coalescence at a low percolation threshold ( Φ C ~0.17) via the formation of fracture-like bubble chains. Percolation was followed by outgassing and bubble collapse causing densification and isolation of the bubble network, resulting in a hysteresis in the evolution of connectivity with porosity. At low melt viscosity and overpressure, we observed a viscous regime with much higher percolation threshold ( Φ C > 0.37) due to spherical bubble growth and lower degree of crystal connection. Finally, our results also show that sintering of crystal-free and crystal-bearing magma analogues is characterised by low percolation thresholds ( Φ C = 0.04 – 0.10). We conclude that the presence of crystals lowers the percolation threshold during vesiculation and may promote outgassing in shallow, crystal-rich magma at initial stages of Vulcanian and Strombolian eruptions.

Textural evolution of magma during the 9.4-ka trachytic explosive eruption at Kilian Volcano, Chaîne des Puys, France - M. Colombier; L. Gurioli; T. H. Druitt; T. Shea; P. Boivin; D. Miallier; N. Cluzel (Bulletin of Volcanology, 2017)